Pengembangan Lembar Kerja Praktikum Digital Berbantuan Virtual Laboratorium pada Materi Pencemaran Air - Destiansari, Elvira; Amizera, Susy; Anggraini, Nike; Arifin, Zainal (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Practicum worksheets have a function as a guide in carrying out a research. Digital-based practicum worksheets assisted by virtual laboratories are currently being developed based on students’ needs on water pollution material. This study aims to analyze the results of material, language, and construct validation in developing digital-based practicum worksheets assisted by virtual laboratories on water pollution material. The type of research used is development research which is limited to the expert review stage. Expert validators consist of three validators, namely: material, language, and construct experts. The results showed that the results of the material expert validation in the first stage were 72.5% (quite valid), then revised and a second validation was carried out which resulted in 92.5% (valid). The results of language validation show results of 80.0% (quite valid), and in the second validation 92.5% (valid). The results of the first construct validation were 69.64% (quite valid), the second 73.21% (quite valid), then the third validation 87.5% (valid). Then proceed with the Co-Kappa analysis showing a result of 0.61 (worksheet can be used). Based on the results of this study, it was concluded that the worksheets developed were valid and categorized as good, so they could be used for the next stage, namely trials.